2022
DOI: 10.3390/dairy3030033
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Individual Glucose Reserves in High-Yielding Dairy Cows

Abstract: Glucose plays a central role in numerous physiological processes in dairy cows related to immune defence and milk production. A lack of glucose impairs both objectives, although to different degrees. A method for the estimation of glucose balance (GB) in dairy cows was developed to assess glucose reserves in the intermediary metabolism. Digestive fluxes of glucogenic carbon were individually estimated via the Systool Web application based on data on body weight (BW), dry matter intake (DMI), and chemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
1
3
0
Order By: Relevance
“…The concentrations of milk fat, milk true proteins, milk lactose, and ECM were similar in both diets. The milk parameters assessed in our study were within acceptable ranges in high-yielding dairy cows, as reported by Ben Meir et al ( 2021) and Habel et al (2022). Our results are also similar to the findings of Saylor et al (2018), who reported a tendency to increase milk protein yield and milk urea nitrogen (MUN) associated with a teff-based diet compared with a control diet.…”
Section: Milk Yield Composition and Efficiency Of Productionsupporting
confidence: 91%
“…The concentrations of milk fat, milk true proteins, milk lactose, and ECM were similar in both diets. The milk parameters assessed in our study were within acceptable ranges in high-yielding dairy cows, as reported by Ben Meir et al ( 2021) and Habel et al (2022). Our results are also similar to the findings of Saylor et al (2018), who reported a tendency to increase milk protein yield and milk urea nitrogen (MUN) associated with a teff-based diet compared with a control diet.…”
Section: Milk Yield Composition and Efficiency Of Productionsupporting
confidence: 91%
“…The main input variables for the calculation of GB were the individual daily milk yield, feed intake and body weight, and data on ration composition and chemical analyses of feedstuffs. Detailed explanations and equations for the calculation of glucose balance are reported elsewhere [ 26 ]. In brief, the calculations have a metabolic and a digestive part.…”
Section: Methodsmentioning
confidence: 99%
“…While the amounts of glucose required for a specific inflammatory condition remain unknown under practical conditions, a methodology indicating the quantities of ‘residual’ glucose available to individual cows (which are expected to reflect a cow’s ability to respond to an inflammatory challenge) has been developed previously. The methodology is described in more detail elsewhere [ 26 ]. Briefly, it encompasses the estimation of the glucose demands of major glucose-consuming tissues (mammary gland, muscle, red blood cells, and the brain) as well as major sources of glucogenic supply (digestive and endogenous) from daily measurements of milk yield, body weight, and feed intake as well as the chemical composition of feedstuffs ingested.…”
Section: Introductionmentioning
confidence: 99%
“…The large amount of non-esterified fatty acids absorbed by the liver exceeds its ability for oxidation and, as a result, encourages liver-related illnesses including fatty liver and ketosis. Additionally, early breastfeeding cows' livers experience metabolic stress due to high rates of hepatic gluconeogenesis, which produces glucose for lactose in the mammary gland [5,6]. In addition to this metabolic stress, early-lactating cows experience a variety of inflammatory challenges, including microbial components (lipopolysaccharides, or LPS), pro-inflammatory cytokines (tumor necrosis factor a (TNF-α), interleukin (IL)-1b, and IL-6), and reactive oxygen species (ROS), as a result of infectious diseases like mastitis and endometritis, as well as subacute [7].…”
Section: Introductionmentioning
confidence: 99%